ИШЧИ КУЧИ БАҲОСИ, ДАРОМАД СОЛИҒИ ВА БАНДЛИКНИНГ ДОЛЗАРБ МАСАЛАЛАРИ (Scientific journal of the Fergana State University, 2023)
The article is devoted to the effective use of the mechanisms of financial and economic instruments to increase the employment of labor in the surplus regions at the present stage of the development of the economic system.